Homocystein: A new biochemical marker in livestock sector - Kozat, Suleyman; Okman, Eda Nur (Journal of Advanced Veterinary and Animal Research, 2018)
The livestock sector is making great contributions to the world economy. Many different diseases, such as cardiovascular diseases, kidney and mineral substance insufficiency, cause huge losses in yield and production in the livestock sector. Early diagnosis is essential to combat these diseases. Today, homocysteine levels are used as biochemical markers in the diagnosis of the functions and diseases of many different organs in human medicine. Homocysteine is an amino acid that occurs in the process of methionine metabolism and does not enter the primary structure of proteins. Homocysteine is a biochemical marker used in the assessment of cardiovascular and renal diseases as well as other organ functions. In this review, homocysteine determination methods and detailed information about which organ and system diseases can be used in livestock sector will be given. http://doi.org/10.5455/javar.2017.d230